Lignin in Suspended Particulate Matter in the Albemarle- Pamlico Estuarine System During the 2018 Hurricane Season - Donini Rivera, Ariana Alexandra (East Carolina University, 2022)
During the 2018 Atlantic hurricane season, North Carolina (NC) was adversely impacted by two major storms: Hurricanes Florence and Michael. Combined, these storms dropped more than 900 mm of precipitation across the entire state and caused flooding along the coast. While both Florence and Michael impacted North Carolina, Hurricane Florence had the greatest impact on coastal NC, which is the focus of this study. This study quantifies particulate lignin, a marker for vascular plants, in water samples collected within the Albemarle Pamlico Estuary System (APES) and coastal ocean adjacent to North Carolina to determine if precipitation during the 2018 hurricane season increased suspended sediments and terrigenous organic matter concentrations in the APES system. Lignin monomers were quantified on glass fiber filters (GFF) using cupric oxide oxidation on samples collected from the APES and the coastal ocean during two time periods: October and November 2018 (~ 6 – 11 weeks post-Florence), and again in July of 2019 (no storm activity). This research allowed for an understanding of the impact of Hurricane Florence, which was one of the largest storms during the 2018 Hurricane Season, on mobilization of terrigenous organic matter into the Albemarle-Pamlico Estuary system. Lignin concentrations in estuarine and coastal suspended sediments in October and November 2018 (14.34 ± 32.40 mg g-1) were considerably higher than estuarine and coastal lignin concentrations in July 2019 (0.34 ± 0.36 mg g-1). Estuarine samples generally had higher lignin concentrations compared to coastal NC samples. Lignin monomer ratios [acid : aldehyde (Ad/Al), syringyl to vanillyl (S/V), and cinnamyl to vanillyl (C/V)] were used determine the sources of terrestrial organic matter into the system as well as the extent of degradation. Based on these, suspended sediments in the 2018 samples consisted of both angiosperm and gymnosperm sources. In contrast, the 2019 suspended sediment samples were solely derived from non-woody angiosperm sources. Generally, lignin on suspended sediments in 2018 was a combination of fresh and highly degraded plant material while in 2019, it was degraded. Samples elevated in the gymnosperm signal only occurred in 2018 and were “fresh” as indicated by lignin acid-aldehyde ratios < 0.8, while samples elevated in angiosperm tissue, found in both 2018 and 2019, were degraded, indicating that the input is coming from both the erosional deposition of gymnosperm vascular plants and the resuspension of already-present sediments. This study suggests that flooding, erosion, and resuspension associated with the 2018 hurricane season did directly affect the concentration of lignin in North Carolina estuarine and coastal systems.
Keywords: Lignin, Albemarle Pamlico Estuarine System, Hurricane, Hurricane Florence, flooding